Accumulation of Lead and Zinc in Earthworm Lampito mauritii (Kinberg): Effect on Survival, Growth and Acetylcholinesterase Activity - Bhattacharya2; Shibani Chaudhury1*, Sulata Maity1, Sonali Roy2, Shelley (Recent Research in Science and Technology, 2010)
Well clitellate earthworm, Lampito mauritii (Kinberg) were exposed to different concentrations (75, 150, 300 mg kg-1) of Pb and Zn separately for 28 days. The effects of the selected metals were studied on survival and growth of the earthworm, Lampito mauritii. In addition to that the levels of Pb and Zn in the specimens were assessed and the response of acetylcholinesterase to metal pollutants was also studied. The results revealed that presence of the Pb and Zn at the selected concentrations did not affect the survival and growth of the earthworm. Pb and Zn were found to gradually accumulate in the earthworm but without recording any significant change in tissue metal concentration after day 14 (Pb 150 and Zn 300 mg kg-1) and day 21 (Pb 75, 300 and Zn 150 mg kg-1). No considerable acetylcholinesterase inhibition was recorded in Zn treated earthworm. Whereas the present study is the evidence of neurotoxic potential of Pb in terms of acetylcholinesterase inhibition though the enzyme activity attains the control level at the end of the experiment. Thus it may be surmised that these low levels of metal treatment do not apparently harm the earthworm in respect of their survival, growth and AChE activity. These factors need to be investigated in future studies with the increasing metal treatment in the soil.